Digital assessment of walking ability: Validity and reliability of the automated figure-of-eight walk test in older adults - Hyun-Ho Kong; Kwangsoo Shin; Dong-Seok Yang; Hye-Young Gu; Hyeon-Seong Joo; Hyun-Chul Shon (PLoS ONE, 2025)
Background The Figure-of-Eight Walk Test (F8WT) can assess straight- and curved-path walking ability, but the validity and reliability of automated measurement of the F8WT using digital device has not yet been studied. The aim of this study was to verify the validity (method comparison) and test-retest reliability of the automated FW8T (aFW8T) using a digital device based on image analysis by comparing the results of the aF8WT with those of the manual F8WT (mF8WT). Methods Community-dwelling older adults underwent the mF8WT performed by a physiotherapist and the aF8WT using the Digital Senior Fitness Test system. To verify the test-retest reliability, the aF8WT was administered again to a randomly selected group of participants one week after the baseline test. The intraclass correlation coefficient (ICC) and Pearson’s correlation analysis were used to verify the degree of agreement between the results of and correlation between the mF8WT and aF8WT, respectively. The 95% confidence interval (CI) of the limits of agreement (LoA) was obtained using Bland–Altman analysis. Results The analysis included 83 participants (mean age 71.6 ± 4.7 years). The participants’ mF8WT and aF8WT results were 29.1 ± 4.9 and 29.8 ± 4.9 seconds, respectively. Pearson’s correlation analysis showed a very strong correlation between the mF8WT and aF8WT results with r = 0.91 (p < 0.001), and the ICC between the mF8WT and aF8WT results was 0.95 (0.91–0.97), showing excellent agreement. The 95% CI of the LoA was ˗0.7 (˗4.8 to 3.3) seconds in the Bland–Altman analysis. In an analysis of the test-retest reliability of the aF8WT, participants’ aF8WT results were 30.9 ± 4.7 seconds (baseline) and 29.6 ± 4.9 seconds (retest), with an ICC of 0.94 (0.81–0.98, p < 0.001), indicating excellent reliability. Conclusion Automated measurement of the F8WT using a digital device showed excellent validity and reliability. The aF8WT can be used to assess and monitor the walking ability of community-dwelling older adults.